Post-traumatic stress, sense of coherence, and growth after the February earthquake: Evidence from teacher training institute students in Syria - Sarmini, Iman Mustafa (Journal of Indonesian Psychological Science (JIPS), 2025)
The current study aims to determine the nature of the relationship between post-traumatic stress disorder, sense of coherence, and post-traumatic growth, as well as their prevalence levels, in light of the experience of students at the Teacher Training Institute, related to the February 6 earthquake. To achieve this, the study's criteria were applied to a sample of 175 students from the Teacher Training Institute, branches (Souran and Mare'), in northwestern Syria. The descriptive correlational approach was adopted. The results showed a high prevalence coefficient for the study variables. There were no gender differences in PTSD and sense of coherence, while females achieved more post-traumatic growth than males. There is also a high positive correlation between sense of coherence and post-traumatic growth in terms of the sub-components and the total score, except the spiritual change component. Furthermore, individuals suffering from PTSD have a low level of sense of coherence. Recommendations: The need to focus on developing guidance programs that stimulate a sense of psychological cohesion and post-traumatic growth to protect young people from psychological disorders.